Aprotinin reduces ischemia-reperfusion injury in the retina of guinea pigs - Yilmaz, T; Kükner, AS; Aydemir, O; Ozercan, HI; Naziroglu, M (Wichtig Editore, 2003)
PURPOSE. The aim of this study was investigate the role of aprotinin on retinal lipid peroxidation and histopathological changes during ischemia/reperfusion (I/R) of guinea pigs. METHODS. Three groups of seven pigmented guinea pigs each were formed: a control (group 1), ischemia/saline (group 2) and ischemia/aprotinin (group 3). One eye of each animal was selected for histopathological evaluation and the other for biochemical assay. Bilateral pressure-induced retinal ischemia was instigated for 90 min and was followed by 24 hours of reperfusion. Animals in the ischemia/aprotinin and ischemia/saline groups received either 20,000 KIU/kg of aprotinin or saline, repeated four times at 6-hour intervals, with the first dose administered 5 min prior to the ischemic insult. The animals were killed at 24 hours of reperfusion. Retinal malondialdehyde (MDA) levels and the thickness of the inner plexiform layers were measured. RESULTS. The level of MDA in group 1 was significantly (p<0.001) lower than the other groups. The mean MDA level in group 2 was significantly (p<0.01) higher than in group 3. The inner plexiform layer in group 1 was significantly (p<0.001) thinner than in the other groups. The mean thickness of the inner plexiform layer in group 2 was significantly (p<0.01) higher than in group 3. CONCLUSIONS. These data indicate that intraperitoneally administrated aprotinin has a protective effect against I/R injury in the retina of guinea pig as evidenced by reduced retinal MDA level and retinal thickness.
Keywords: ischemia-reperfusion injury; retina; aprotinin